Living with Legacy: Outcomes and Future Implications for Offspring of Patients with MEN1 - Muthukuda, Dimuthu Tharanga; Jayawickreme, Kushalee Poornima; Wijeweera, Gayathri; Grossman, Ashley (Journal of the ASEAN Federation of Endocrine Societies, 2026)
Background. Multiple endocrine neoplasia type 1 (MEN1) is a hereditary condition with an autosomal dominant inheritance, with a predisposition to both endocrine and non-endocrine tumours. MEN1-related tumours can appear as early as the age of five, with disease penetrance increasing with age. Offspring of a MEN1 parent shows a 50% probability of inheriting the MEN1-related gene mutation. A MEN1 diagnosis in a parent can lead to significant anxiety for both the diagnosed parent and their undiagnosed at-risk children. There is limited consensus specific for managing offspring of individuals diagnosed with MEN1. Objectives. This review aims to evaluate the existing literature on the outcomes of MEN1 syndrome in the offspring of affected patients, to identify gaps in current protocols and to suggest possible improvements. Methodology. A literature review was conducted to examine the outcomes and characteristics of the offspring of individuals diagnosed with MEN1. Results. Predictive testing and screening for organ involvement in MEN1 aid early diagnosis and timely interventions. DNA testing is recommended for children within the first decade of life, and screening for organ involvement should ideally begin at age 5 years for all MEN1 mutation carriers. Manifestations of MEN1 in younger children are different from those of affected adults. Conclusions. Standardised, internationally-accepted guidelines that provide specific recommendations for screening, diagnosis and treatment of offspring of adults diagnosed with MEN1 is a timely need. Furthermore, the absence of national and international data pooling across regions remains a serious limitation, impeding the ability to draw conclusions from larger, more representative patient populations.